Understanding Critical Race Research Methods and Methodologies: Lessons from the Field, 1st edition - Jessica T. , DeCuir-Gunby (Routledge, 2020)
Despite the growing urgency for Critical Race Theory (CRT) in the field of education, the "how" of this theoretical framework can often be overlooked. This exciting edited collection presents different methods and methodologies, which are used by education researchers to investigate critical issues of racial justice in education from a CRT perspective. Featuring scholars from a range of disciplines, the chapters showcase how various researchers synthesize different methods—including qualitative, quantitative and mixed methods, and historical and archival research—with CRT to explore issues of equity and access in the field of education. Scholars discuss their current research approaches using CRT and present new models of conducting research within a CRT framework, offering a valuable contribution to ongoing methodological debates. Researchers across different levels of expertise will find the articulations of CRT and methods insightful and compelling.